2018
DOI: 10.1002/lno.11036
|View full text |Cite
|
Sign up to set email alerts
|

Comment. What drives plankton seasonality in a stratifying shelf sea? Some competing and complementary theories

Abstract: The Plymouth L4 time plankton series in the Western English Channel is a textbook example of a shallow, stratifying shelf sea system. Over its 30 yr of weekly sampling, this site has provided a diverse and contrasting suite of numerical and conceptual models of plankton bloom formation, phenology, and seasonal succession. The most recent of these papers, Kenitz et al. (2017) has initiated this comment, partly because we feel that it has presented a slightly misleading picture of the plankton composition at thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…emerge from the complex interactions of the ecosystem itself where any given player is exposed to top‐down and bottom‐up pressures. In a comment to our recent manuscript (Kenitz et al ), Atkinson et al () rightly point out that no single mechanism is likely to explain observed variations, and we support their call to carefully reconsider how seasonal plankton dynamics are described and modeled.…”
Section: Seasonalitysupporting
confidence: 55%
See 1 more Smart Citation
“…emerge from the complex interactions of the ecosystem itself where any given player is exposed to top‐down and bottom‐up pressures. In a comment to our recent manuscript (Kenitz et al ), Atkinson et al () rightly point out that no single mechanism is likely to explain observed variations, and we support their call to carefully reconsider how seasonal plankton dynamics are described and modeled.…”
Section: Seasonalitysupporting
confidence: 55%
“…In reality, variability in species distribution is controlled by multitude of interacting processes that swing in and out of prominence on temporal and spatial scales. In our response, we would like to echo the main message of Atkinson et al () comment: there is a tremendous need to combine the suggested mechanisms to investigate their cumulative effects on shaping plankton community structure. In this, the L4 station time series provides an invaluable resource that traces 30 years of highly resolved physical and biological observations.…”
Section: Seasonalitymentioning
confidence: 92%
“…by size-based analysis, are not captured in conceptual or simulation models of L4 seasonality (Atkinson et al 2018). The models tend to overemphasize the spring diatom bloom, a relatively indistinct feature in the size spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, plankton and environmental data from Station L4 did not neatly conform either to the singleor the double-integration models proposed by Di Lorenzo & Ohman (2013) for long-lived krill (1−2 yr) in the California Current Ecosystem. The California Current region is an upwelling system with strong decadal changes in geostrophic transport (Bograd et al 2001), whereas Station L4 is a dynamic inshore, albeit seasonally stratified continental shelf ecosystem (Atkinson et al 2018). It is therefore not surprising that these systems, with strongly contrasting physical dynamics and plankton communities, would have different pathways linking atmospheric and ecological variability.…”
Section: Discussionmentioning
confidence: 99%